Complete Genomic Analysis of Enterococcus faecium Heat-Resistant Strain Developed by Two-Step Adaptation Laboratory Evolution Method - Min, Bonggyu; Yoo, DongAhn; Lee, Youngho; Seo, Minseok; Kim, Heebal (Frontiers in Bioengineering and Biotechnology, 2020)
Stress resistance is important in food manufacturing processes that use lactic acid bacteria. In particular, high temperature is a key factor that negatively affects bacterial growth and even leads to cell death. Development of heat-resistant strains continues, but developmental studies accompanying genomic analysis to identify the causal factors of the resistance mechanisms are still insufficient. Furthermore, it is necessary to develop strains with tolerance to multiple stresses. Herein, we isolated one Enterococcus faecium strain named BIOPOP-3 and completed a full-length genome sequence. Using this strain as a wild type, a two-step adaptive laboratory evolution (ALE) method was applied to obtain a heat-resistant strain, BIOPOP-3 ALE. After sequencing the whole genome, we compared two full-length sequences and identified five non-synonymous variants that could confer heat resistance, which were technically validated by resequencing. We experimentally verified that the evolved strain was significantly enhanced in not only heat resistance but also acid and bile resistance. We demonstrated that the developed heat-resistant strains can be applied in animal feed manufacturing processes. The multi-stress-resistant BIOPOP-3 ALE strain developed in this study and the two-step ALE method are expected to be widely applied in industrial and academic fields. In addition, we expect that the identified variants which occurred specifically in heat-resistant strain will enhance molecular biological understanding and be broadly applied to the biological engineering field.